Nephromyces Encodes a Urate Metabolism Pathway and Predicted Peroxisomes, Demonstrating That These Are Not Ancient Losses of Apicomplexans. (30th November 2018) - Paight, Christopher; Slamovits, Claudio H; Saffo, Mary Beth; Lane, Christopher E
Abstract: The phylum Apicomplexa is a quintessentially parasitic lineage, whose members infect a broad range of animals. One exception to this may be the apicomplexan genus Nephromyces, which has been described as having a mutualistic relationship with its host. Here we analyze transcriptome data from Nephromyces and its parasitic sister taxon, Cardiosporidium, revealing an ancestral purine degradation pathway thought to have been lost early in apicomplexan evolution. The predicted localization of many of the purine degradation enzymes to peroxisomes, and the in silico identification of a full set of peroxisome proteins, indicates that loss of both features in other apicomplexans occurred multiple times. The degradation of purines is thought to play a key role in the unusual relationship between Nephromyces and its host. Transcriptome data confirm previous biochemical results of a functional pathway for the utilization of uric acid as a primary nitrogen source for this unusual apicomplexan.